Relationship between Hospital 30‐Day Mortality Rates for Heart Failure and Patterns of Early Inpatient Comfort Care. Issue 3 (1st March 2018) - Chen, Lena M.; Levine, Deborah A.; Hayward, Rodney; Cox, Margueritte; Schulte, Phillip J.; DeVore, Adam D.; Hernandez, Adrian; Heidenreich, Paul A.; Yancy, Clyde; Fonarow, Gregg C.
Abstract : BACKGROUND: The Centers for Medicare & Medicaid Services rewards hospitals that have low 30‐day risk‐standardized mortality rates (RSMR) for heart failure (HF). OBJECTIVE: To describe the use of early comfort care for patients with HF, and whether hospitals that more commonly initiate comfort care have higher 30‐day mortality rates. DESIGN: A retrospective, observational study. SETTING: Acute care hospitals in the United States. PATIENTS: A total of 93, 920 fee‐for‐service Medicare beneficiaries admitted with HF from January 2008 to December 2014 to 272 hospitals participating in the Get With The Guidelines‐Heart Failure registry. EXPOSURE: Early comfort care (defined as comfort care within 48 hours of hospitalization) rate. MEASUREMENTS: A 30‐day RSMR. RESULTS: Hospitals' early comfort care rates were low for patients admitted for H F, with no change over time (2.5% to 2.6%, from 2008 to 2014, P = .56). Rates varied widely (0% to 40%), with 14.3% of hospitals not initiating comfort care for any patients during the first 2 days of hospitalization. Risk‐standardized early comfort care rates were not correlated with RSMR (median RSMR = 10.9%, 25th to 75th percentile = 10.1% to 12.0%; Spearman's rank correlation = 0.13; P = .66). CONCLUSIONS: Hospital use of early comfort care for HF varies, has not increased over time, and on average, is not correlated with 30‐day RSMR. This suggests that current efforts to lower mortality rates have not had unintended consequences for hospitals that institute early comfort care more commonly than their peers.